Conceptual and procedural knowledge of junior high school students through realistic mathematics education (RME) approach. (February 2020) - Maulina, R; Zubainur, C M; Bahrun,
Abstract: Mathematics learning that provides the ready-made concepts and procedures without involving students in re-invention the concepts. RME approach is a solution for upgrading the students' competency in reconstructing the concepts and creating the procedures to solve the mathematical problems. This research aims to identify the students' conceptual and procedural knowledge through the RME approach based on the students' ability level. This study used a mixed-method and involved the Year 7 students as the sample. The data were analyzed using percentage and explained descriptively. The results indicated that the percentage of the procedural knowledge of the high and medium-achieving students was 80%, categorized as very good, while the percentage of the low-achieving students was 42.8% (adequate). The conceptual knowledge of the high, medium and low-achieving students was very good (84%), good (72.7%) and adequate (42.8%). The conceptual knowledge of the low-achieving students was higher than their procedural knowledge by 2, 8%. The results showed that the medium-achieving students tended to be varied and flexible in applying their ideas to solve the procedural problems, meanwhile the high-achieving students inclined to memorize the concept and use a formula in solving the problems.